Etika Berinteraksi Dengan Al-Qur’an: Studi Analisis Pemikiran Mahmud Ad-Dausary Dalam Kitab Hajr Al-Qur’an Al-Azhim Anwa’uhu Wa Ahkamuhu - Muhammad Habibullah; Akhmad Sulthoni; Akhmadiyah Saputra (Yayasan Sembilan Pemuda Indonesia, 2025)
This study focuses on Mahmud Ad-Dausary’s thoughts on the ethics of interacting with the Qur’an with reference to his work “Hajr Al-Qur’an Al-’Azhim: Anwa’uhu Wa Ahkamuhu”. This study employs a qualitative method with a descriptive-analytical approach. Primary data is sourced from the book Hajr Al-Qur’an Al-’Azhim, while secondary data includes tafsir books, journals, and other scholarly works. The results of the study indicate that Mahmud Ad-Dausary addresses this issue in depth by dividing ethics into two aspects: negative ethics, which includes various forms of neglect toward the Qur’an, and positive ethics, such as etiquette when listening to the Qur’an and etiquette in reciting the Qur’an, which includes sincere intention, purification, reciting with proper pronunciation, reflecting on the meaning, and putting it into practice. Through proper etiquette, the relationship with revelation becomes more meaningful, not only in words but also permeating attitudes and actions. Mahmud Ad-Dausary’s intellectual contributions demonstrate that the integration of spiritual values and ethics in interacting with the Qur’an can serve as a solution to the ethical challenges of engaging with the Qur’an in the modern world, as well as providing a framework that supports sustainability in contemporary research.